Contemporary comics by Jewish women. Issue 2 (1st December 2015) - Bauer, Heike; Greenbaum, Andrea; Lightman, Sarah
'Contemporary comics by Jewish women' brings together essays, interviews and original artwork by or about Jewish women comics artists. In this Introduction we reflect on our own approach investment in this project, and in so doing also explain the scope and content of this special issue.